Metastatic Patterns of Myxoid/Round Cell Liposarcoma: A Review of a 25-Year Experience. (1st April 2012) - Asano, Naofumi; Susa, Michiro; Hosaka, Seiichi; Nakayama, Robert; Kobayashi, Eisuke; Takeuchi, Katsuhito; Horiuchi, Keisuke; Suzuki, Yoshihisa; Anazawa, Ukei; Mukai, Makio; Toyama, Yoshiaki; Yabe, Hiroo; et al.
Abstract : Myxoid/round cell liposarcoma (MRCL), unlike other soft tissue sarcomas, has been associated with unusual pattern of metastasis to extrapulmonary sites. In an attempt to elucidate the clinical features of MRCL with metastatic lesions, 58 cases, from the medical database of Keio University Hospital were used for the evaluation. 47 patients (81%) had no metastases, whereas 11 patients (11%) had metastases during their clinical course. Among the 11 patients with metastatic lesions, 8 patients (73%) had extrapulmonary metastases and 3 patients (27%) had pulmonary metastases. Patients were further divided into three groups; without metastasis, with extrapulmonary metastasis, and with pulmonary metastasis. When the metastatic patterns were stratified according to tumor size, there was statistical significance between the three groups (P = 0.028 ). The 8 cases with extrapulmonary metastases were all larger than 10 cm. Similarly, histological grading had a significant impact on metastatic patterns (P = 0.027 ). 3 cases with pulmonary metastatic lesions were all diagnosed as high grade. In conclusion, large size and low histological grade were significantly associated with extrapulmonary metastasis.